Students’ Perception Toward The Use Of Process Approach In Writing Course of English Department in Mulawarman University - Nira Miranda; Aridah Aridah; Syamdianita (E3L: Journal of English Language Teaching, Linguistics, and Literature, 2021)
This study was aimed (1) to find out how the process approach is implemented in writing course and (2) to know the students’ perceptions toward the use of process approach in writing course. The design of this study was a descriptive qualitative design. The data were collected by using interview guide. The 64 students from class B 2018 and C 2019 were selected as the subject from the results of final score in writing 3 course. While, the six students were selected as the interviewee since they had the highest, middle, and lowest score in writing class. The result of this study found that the lecturer used the same five steps of process approach based on Hyland (2003) which involved pre-writing, drafting, revising, editing and publishing. Furthermore, the students’ perception toward the use of process approach in writing course was totally positive. It was explicitly described under the five aspects that were attitudes, motives, interests, experience, and expectation. Mostly, the students showed positive perception toward the use of process approach in writing course. Moreover, the implementation of process approach was very helpful and also motivated them in writing their future essay